COVID-19 Pandemic and MSMEs in Indonesia: Impact and Policy Responses - Gunadi, Ahmad Dading; Lesmana, Harry; Fachrizah, Hilda; Revindo, Mohamad Dian; Daniswara, Rama Vandika (Jurnal Ekonomi Indonesia, 2021)
Since the first confirmed case of COVID-19 infection in Indonesia in March 2020, the pandemic has hit the economy hard, especially the Micro, Small and Medium-sized Enterprises (MSMEs). This study aims to analyze the extent of the impact of the pandemic on MSMEs and the effectiveness of the government policy measures. Primary data was collected through a questionnaire administered to 2,535 MSMEs in 17 provinces during July–September 2020. The results show that MSMEs already suffered revenue slump within the second month of the pandemic and encountered both financial and non-financial hardships. The government supports and assistance was perceived as very helpful to mitigate the impact of the pandemic by the recipients. However, the programs’ distribution was hampered by either mis-targeting or lack of socialization regarding applicationrequirements, procedures and registration location. The policy, academic and managerial implications of the findings are provided.